Mycobacterium tuberculosis complex differentiation using gyrB-restriction fragment length polymorphism analysis - Chimara, Erica (2015)
Mycobacterium tuberculosis complex (MTBC) members are causative agents of human and animal tuberculosis. Differentiation of MTBC members is required for appropriate treatment of individual patients and for epidemiological purposes. Strains from six MTBC species - M. tuberculosis, M. bovis subsp. bovis, M. bovis BCG, M. africanum, M. pinnipedii, and M. canetti - were studied using gyrB-restriction fragment length polymorphism (gyrB-RFLP) analysis. A table was elaborated, based on observed restriction patterns and published gyrB sequences. To evaluate applicability of gyrB-RFLP at Instituto Adolfo Lutz, São Paulo, Mycobacterial Reference Laboratory, 311 MTBC clinical isolates, previously identified using traditional methods as M. tuberculosis (306), M. bovis (3), and M. bovis BCG (2), were analyzed by gyrB-RFLP. All isolates were correctly identified by the molecular method, but no distinction between M. bovis and M. bovis BCG was obtained. Differentiation of M. tuberculosis and M. bovis is of utmost importance, because they require different treatment schedules. In conclusion, gyrB-RFLP is accurate and easy-to-perform, with potential to reduce time needed for conventional differentiation methods. However, application for epidemiological studies remains limited, because it cannot differentiate M. tuberculosis from M. africanum subtype II, and M. canetti, M. africanum subtype I from M. pinnipedii, and. M. bovis from M. bovis BCG.